2020
DOI: 10.21203/rs.2.14562/v7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and associations of active trachoma among rural preschool children in Wadla district, northern Ethiopia

Abstract: Background: Trachoma is a neglected eye disease and an important cause of preventable corneal blindness. In endemic areas, initial infection can occur in early childhood and following a recurrent episodes, it progresses to scarring and visual impairment. Trachoma disappeared from high income countries through enhancements of hygiene and sanitation but the disease is still a challenge in developing countries. In Ethiopia, data indicate that Amhara is the region with the highest prevalence of active trachoma. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, a child from a family who did not have a latrine in the compound had nearly four times greater odds of developing clinically active trachoma than those who had a latrine in their compound. This nding is consistent with different studies; a study from Wadla District showed that ve times, and a study from Areka District showed a nearly seven times greater likelihood of developing clinically active trachoma when compared with children from households with a latrine (10,23). However, this value was lower than that reported in a study from Gazagibela District, which reported a 12.9-fold greater probability of developing clinically active trachoma (27).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, a child from a family who did not have a latrine in the compound had nearly four times greater odds of developing clinically active trachoma than those who had a latrine in their compound. This nding is consistent with different studies; a study from Wadla District showed that ve times, and a study from Areka District showed a nearly seven times greater likelihood of developing clinically active trachoma when compared with children from households with a latrine (10,23). However, this value was lower than that reported in a study from Gazagibela District, which reported a 12.9-fold greater probability of developing clinically active trachoma (27).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the vector bazaar y will reach a comfortable zone for spreading disease-causing microorganisms. Therefore, the prevalence is high in this age group (3,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation